Size-dependent flame retardancy of black phosphorus nanosheets. Issue 7 (9th February 2022) - Duan, Zunbin; Wang, Yanfang; Bian, Shi; Liu, Danni; Zhang, Yanli; Zhang, Xue; He, Rui; Wang, Jiahong; Qu, Guangbo; Chu, Paul K.; Yu, Xue-Feng
Abstract : The uniformly dispersed black phosphorus nanosheets with an appropriate size in the epoxy resin improve flame retardancy. Abstract : Two-dimensional black phosphorus (BP) nanosheets are potential flame-retardant nano-additives. Herein, the effects of the size of BP nanosheets embedded in epoxy resin (EP) on flame retardancy are studied. BP nanosheets with four different sizes are synthesized from bulk BP by different exfoliation methods including solid ball milling, liquid ball milling, ultrasonic liquid exfoliation, and electrochemical exfoliation (samples are designated as sb-BP, lb-BP, us-BP, and ec-BP, respectively). lb-BP exhibits the best dispersion in the EP matrix, and the lb-BP/EP composite shows the best flame-retardancy properties among the four BP/EP composites. Compared to bare EP, lb-BP/EP shows obvious improvements including the reduction in the heat release peak rate by 34.4%, total heat release by 27.0%, peak of smoke production rate by 69.2%, and total production of carbon monoxide by 50.8%. The mechanistic study reveals that lb-BP serves as a barrier and carbonization catalyst to delay combustion. These results confirm the size dependence of flame-retardancy properties of BP nanosheets and the new knowledge provides insights into the size dependent effects of other two-dimensional materials.